The Power of Positional Concerns - Benno Torgler; Sascha L. Schmidt; Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2008)
People care a great deal about their relative economic position and not solely about their absolute economic position. However, behavioral evidence is rare. This paper provides evidence on how the relative income position affects professional sports performances. Our analysis suggests that if a player's salary is below the average and this difference increases, his performance worsens. Moreover, the larger the income differences, the stronger positional concern effects are observable. We also find that the more the players are integrated, the more evident a relative income effect is. Finally, we find that positional effects are stronger among high performing teams.
Keywords: 330; Relative income; positional concerns; organizational justice; envy; social comparison; relative derivation; equity theory; prospect theory; loss aversion; performance